Role of Integrin αvβ3 in Vascular Biology - Byzova, Tatiana V.; Rabbani, Ramin; D’Souza, Stanley E.; Plow, Edward F. (Thrombosis and Haemostasis, 1998)
A defining characteristic of vascular cells is their adhesive status. The predominant cells of the blood vessel, endothelial cells (EC) and smooth muscle cells (SMC), are normally adherent but can be induced to migrate in response to vascular injury and angiogenic stimuli. The circulating blood cells are ordinarily nonadhesive but can rapidly acquire an adhesive phenotype in response to physiologic and pathophysiologic stimuli. As prime examples, platelets become adherent to the subendothelial matrix and to one another during thrombus formation, and leukocytes first adhere to EC and then transmigrate during the inflammatory response. At a molecular level, the adhesive properties of the vascular cells are determined by the adhesion receptors on their cell-surface and the functional state of these receptors. To match the variety of requisite cellular adhesive reactions, the repertoire of adhesion receptors expressed by vascular cells is broad. Multiple representatives of the immunoglobulin-like, the selectin, the cadherin and the integrin families of adhesion receptors are present on and have been implicated in the functions of the vascular cells. The importance of these adhesion receptors in vascular cell function is underscored by the severe pathogenetic consequences of their congenital deficiencies, such as in Glanzmann’s thrombasthenia, LAD (Leucocyte Adhesion deficiency) I and LAD II (1-3).The integrins are the largest and most broadly distributed of the families of cellular adhesion receptors. Of the integrins, αvβ3, originally identified as the vitronectin receptor, is particularly widely distributed. It is expressed at variable density on many types of vascular cells. Obviously, the adhesive properties of a cell are determined by its full repertoire of adhesion receptors. As an example, the adhesion of EC to fibrinogen/fibrin is mediated by no fewer than five receptors. Nevertheless, it is possible to dissect out the contributions of individual adhesion receptors, and αvβ3 has been implicated in many functional responses of vascular cells. This review focusses upon the role of αvβ3 in vascular cell biology. Other contributions of this multifunctional receptor, such as its role in neoplastic growth and invasion and in osteoclast-mediated bone resorption, are beyond the scope of this article and have been reviewed elsewhere (4, 5).